Cell Attachment Capacity and Compounds of Fibrin Membranes Isolated from Fresh Frozen Plasma and Cryoprecipitate - Adél Hinsenkamp; Kiara Kun; Fatime Gajnut; Aliz Majer; Zsombor Lacza; István Hornyák (Membranes, 2021)
Fibrin membranes are widely used in regenerative medicine because they are biocompatible, biodegradable, contain growth factors, and support cell attachment. Most commonly they are produced from serum, but they can also be isolated from activated plasma. To increase the fibrinogen concentration of plasma, cryoprecipitate isolation is a possible solution. In this work, cryoprecipitate was prepared from fresh frozen plasma, isolated by plasmapheresis. The concentration of cellular elements, fibrinogen, total protein, and immunoglobulins among others was measured in different concentrations of cryoprecipitates. After activation with Ca-gluconate, fibrin membranes were produced in different thicknesses, and human mesenchymal stem cells were seeded onto the membranes. They were visualized by live-dead staining and their viability was determined by XTT. The platelet-derived growth factor AB content was quantified by ELISA. Our results showed that fibrinogen and platelet concentration can be multiplied in plasma by cryoprecipitate isolation, which affects the thickness and slightly the growth factor content of the membranes. According to live-dead staining, the thickness of the membranes does not influence cell attachment, and XTT measurement did not reveal a significant difference in cell attachment capacity either; however, a growing trend could be observed in the case of some membranes.